2000
DOI: 10.1111/j.1528-1157.2000.tb06044.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost Minimization Analysis of Antiepileptic Drugs in Newly Diagnosed Epilepsy in 12 European Countries

Abstract: Summary: A recent United Kingdom cost minimization analysis (CMA) of four antiepileptic drugs (AEDs) used to treat newly diagnosed adult epilepsy demonstrated that a new drug, lamotrigine (LTG), incurred higher costs than carbamazepine (CBZ), phenytoin (PHT), and valproate (VPA), whose costs were similar. This analysis took account of each drug's sideeffect and tolerability profile. The present analysis investigated the costs of treatment with LTG, CBZ, PHT, and VPA in 12 European countries. Data were derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Heaney and colleagues 253 report the costs in the first 2 years of initiating therapy, based on the trials and from an ITT perspective, to vary between £795 and £829 for CBZ, £736 and £768 for PHT, £868 and £884 for VPA and £1525 and £2076 for LTG. Heaney and colleagues 254 estimate that treating a patient with LTG as first-line therapy is between two and four times as expensive as treatment with CBZ, PHT or VPA, which share similar costs, over the first year. These results are consistent in all countries considered despite variations in the medical management of epilepsy.…”
Section: Monotherapymentioning
confidence: 99%
See 3 more Smart Citations
“…Heaney and colleagues 253 report the costs in the first 2 years of initiating therapy, based on the trials and from an ITT perspective, to vary between £795 and £829 for CBZ, £736 and £768 for PHT, £868 and £884 for VPA and £1525 and £2076 for LTG. Heaney and colleagues 254 estimate that treating a patient with LTG as first-line therapy is between two and four times as expensive as treatment with CBZ, PHT or VPA, which share similar costs, over the first year. These results are consistent in all countries considered despite variations in the medical management of epilepsy.…”
Section: Monotherapymentioning
confidence: 99%
“…253 The same authors, in collaboration with others, assessed five RCTs for a European study that was published in 2000. 254 …”
Section: Treatment Of Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…A good example of cost-minimization analysis is the European study in which four epilepsy drugs (lamotrigine, carbamazepine, phenytoin and valproate), equally effective in terms of their ability to achieve seizure freedom, were compared with regard to price [2]. It was found that lamotrigine was more costly than the other three [2].…”
Section: Cost-minimization Analysismentioning
confidence: 98%